Solve n: 2(n+7) = n - 3
First: eliminate parenthesis --- distribute the outer term with terms in parenthesis....
2(n) + 2(7) = n - 3
2n + 14 = n - 3
Sec: combine "like" terms --- subtract "n" from both sides (when you move a term to the opposite side, always use the opposite sign)....
2n + 14 - n = n - n - 3
2n + 14 - n = - 3
2n - n + 14 = - 3
n + 14 = - 3
Third: isolate "n" on one side --- subtract 14 from both sides....
n + 14 - 14 = - 3 - 14
n = - 3 - 14
n = -17
2007-02-13 03:19:25
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
0⤊
1⤋
Well first you use the distributive property for the 2(n+7) With that you do 2 times n and 2 times 7. So due to that and the addition sign, it would be 2n+14=n-3.
Then you would move the n on the right side of the equation and put it with the 2n. Because of the rule when crossing over the equal sign, the number becomes its opposite instead of the n remaining positive and making the 2n a 3n, it's negative and it makes the 2n a 1n. So now the equation reads 1n+14= -3. Now you move the 14 and combine it with the -3. Once again in becomes -14 because of it crossing the equal sign. So -14+-3=-17. The equation now reads n= -17 and that's the answer.
So the final answer is -17
2007-02-16 13:41:53
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
2 ( n + 7 ) = n - 3 => 2n + 14 = n - 3
2n - n = - 3 - 14
n = - 17
2007-02-13 11:20:01
·
answer #3
·
answered by Cool Sun 3
·
0⤊
0⤋
(The person above me forget the negative on the 3)
Use the distributive property.
2n + 2(7) = n - 3
2n + 14 = n - 3
2n - n = - 3 - 14
n = -17
2007-02-13 11:17:14
·
answer #4
·
answered by teekshi33 4
·
1⤊
0⤋
2(n + 7) = n - 3
2n + 14 = n - 3
n + 14 = -3
n = -3 - 14
n = -17
2007-02-13 11:46:33
·
answer #5
·
answered by Como 7
·
0⤊
0⤋
2n + 2(7) = n - 3
2n + 14 = n - 3
2n - n = - 3 - 14
n = -17
2007-02-13 11:22:13
·
answer #6
·
answered by Krish 5
·
0⤊
0⤋
Multiply 2 times what is in the parethesis.
2n+14=n-3
now get the n alone.
2n-n= -14-3
n=-17
2007-02-13 11:17:48
·
answer #7
·
answered by Saucy 3
·
0⤊
0⤋
First, multiply the 2 through on the left:
2n + 14 = n - 3
Now move all the n to one side:
2n - n + 14 = 3
n + 14 = 3
now move all the other numbers to the other side:
n = 3 - 14
n = -11
2007-02-13 11:17:02
·
answer #8
·
answered by Mathematica 7
·
0⤊
3⤋
it is a silly qusetion ....
2(n+7)=n-3
2n+14=n-3
2n-n=-3-14
n= -17
2007-02-15 01:46:32
·
answer #9
·
answered by శేఖర్ భట్టు 1
·
0⤊
0⤋
n=-17
2007-02-13 11:22:34
·
answer #10
·
answered by cleatus 1
·
0⤊
0⤋